The Effectiveness of Material Based Stories in Improving Students Reading Comprehension - Hasan, Hasan; Ismail, Ismail (Majesty Journal, 2022)
This research was intended to explain the students reading comprehension through material based stories at the eighth grade of SMP Negeri 1 Maiwa Kabupaten Enrekang in the 2018/2019 academic year. This research used a quasi-experimental method class. It had conducted into two groups namely the experimental group and control group. The Sample in this research were 44 students. The researcher took real data from class to know the students reading comprehension. The instrument of this research was pre-test-posttest with multiple choice, T/F and read test. From these findings, there was a significant effect on the students reading comprehension through material based stories. The data was analyzed by using a t-test and the result showed that the t-test value 4.629 was higher than the t-table value 2.021. It meant that there was a significant difference between students’ reading achievement before and after the treatment through the stories. It concluded that material based stories can be used in improving the reading comprehension of the students.